The effect of grammatical structure in directing meaning the poem (I see you are refractory to escape tears) is an example (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
The grammatical structure constituted a fertile field for grammatical and rhetorical studies. Therefore, it is aesthetically pleasing to study it with an exceptional poet, He is Abu Firas Al-Hamdani, whose poem (I See You as Sticks of Tears) was a starting point for demonstrating the eloquence of grammar, and the eloquence between the structures of this poem and its meaning, Because it contains in its systems the strength of words and meanings, the sobriety of rhymes, and the clarity of expressions and structures, even if they contain ambiguity in some aspects, It is a transparent mystery that enriches and tempts the reader, and draws him to delve deeper into the beauty of poetic images that constitute an important part of the vertical plane, The structure of this poem is unique in a solid way, full of facets, and in every facet there is a significance, and in every significance there is a powerful resonance.Every part of the poem has revealed the characteristics of the civilized Abbasid era, full of luxury and chivalry, and the luxury of the era merged with the life of Abu Firas Al-Hamdani, which was full of orphanhood, Filled with the desire to make amends and reach the highest positions, fate had no choice but to put him in the arena of confrontation with the families, Which prompted him to compose the poem (I See You as Sticks of Tears); To be a mirror that shows us the art of spinning and pride, with a philosophy that Al-Hamdani pushes us to delve deeper into its taste.